Determinants of EMNEs' entry mode decision with environmental volatility issues: A review and research agenda - Yameng Li; Ruosu Gao; Jingyi Wang (Journal of Risk and Financial Management, 2021)
Emerging market multinational enterprises (EMNEs) play a vital role in global economic development and usually adopt aggressive internationalization strategies. However, the volatile global environment has caused EMNEs to face various risks in their overseas expansion. To maximize the competitive advantages and achieve successful expansion, EMNEs should choose the most suitable foreign entry mode. Therefore, EMNEs need to understand what environmental factors affect their decision-making and how they influence the choice of entry modes, especially in a volatile environment. This review examines 44 selected journal articles from 1996 to June 2021 on the environmental volatility determinants of EMNEs' entry mode choice. The entry mode choice we examined is mainly wholly-owned subsidiary versus international joint venture. We categorized the environmental volatility determinants investigated in the literature we reviewed into country-level factors (such as cross-national distance) and industry-level factors (such as industry condition). The main contributions are: (1) the review reveals three research gaps in extant studies, which are lack of research on external environmental factors, lack of research on multinationals from less concerning emerging economies, and lack of research on small-to-medium (SMEs) enterprises. (2) Practically, the study highlights the importance of understanding external environmental factors for EMNEs to make the most suitable entry mode decisions.
Keywords: 330; emerging multinational enterprise; entry mode; environmental volatility; systematic literature review; wholly-owned subsidiary; international joint venture